2015
DOI: 10.3923/ajppaj.2015.46.58
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Trichoderma spp. as Biological Control Agents Against Bakanae Pathogen (Fusarium fujikuroi) in Rice

Abstract: Bakanae disease is a major rice disease caused by Fusarium fujikuroi. Infected plants show slender and hyper elongated internodes due to the over-production of gibberellic acid. Application of Trichoderma spp. as biocontrol agent is gaining attention due to high capability in hyperparasitize the soil borne pathogen. The studies aimed to screen and evaluate the bio-efficacy of Trichoderma spp. with antagonistic activities against F. fujikuroi and plant growth-promoting properties. All the 65 Trichoderma isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…However, the ability of Trichoderma species depends on the kind and strain of Trichoderma and source of phosphate (Kapri and Tewari, 2010;Promwee, 2011). Our finding was also supported by many workers (Rawat and Tewari, 2011;Promwee et al, 2014;Ng et al, 2015) who reported that even though Trichoderma species revealed good mycelia growth, there was no formation of halo-zone on the solid medium containing insoluble inorganic phosphorus source. In addition, Nautiyal (1999) reported that the criterion for isolation of phosphate solubilizers based on the formation of a visible halo-zone on Pikovskaya's agar is not a reliable technique because many isolates of Phosphate Solubilizing Microorganisms (PSM), which did not show any clear zone on agar plates, could be able to solubilize insoluble inorganic phosphates in liquid medium.…”
Section: Phosphate Solubilizing Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…However, the ability of Trichoderma species depends on the kind and strain of Trichoderma and source of phosphate (Kapri and Tewari, 2010;Promwee, 2011). Our finding was also supported by many workers (Rawat and Tewari, 2011;Promwee et al, 2014;Ng et al, 2015) who reported that even though Trichoderma species revealed good mycelia growth, there was no formation of halo-zone on the solid medium containing insoluble inorganic phosphorus source. In addition, Nautiyal (1999) reported that the criterion for isolation of phosphate solubilizers based on the formation of a visible halo-zone on Pikovskaya's agar is not a reliable technique because many isolates of Phosphate Solubilizing Microorganisms (PSM), which did not show any clear zone on agar plates, could be able to solubilize insoluble inorganic phosphates in liquid medium.…”
Section: Phosphate Solubilizing Activitysupporting
confidence: 90%
“…This is mainly due to cyanide production by microbes which can acts as a general metabolic inhibitor to avoid predation or competition without harming the host plants (Noori and Saud, 2012.). The result of the present investigation is also supported by Aarti and Meenu (2015), Ng et al, (2015) and Mohiddin et al, (2017) who reported the positive production of HCN by Trichoderma spp.…”
Section: Hydrogen Cyanide (Hcn) Productionsupporting
confidence: 90%
“…The antagonic effects of the genus Trichoderma have been reported in several phytopathogens of economic importance (Woo et al, 2014) including Phytophthora infestans (Kerroum et al, 2015), Fusarium fujikuroi (Ng et al, 2015) (Naglot et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…e behavior of this strain should be investigated against phytopathogenic fungi such as, for example, Fusarium oxysporum, Botrytis cinerea, Crinipellis perniciosa, and Rhizoctonia solani [12,13,32,33]. For this reason, it is important to produce 6-PP, conidia, or biomass in large amounts to meet field requirements.…”
Section: Discussionmentioning
confidence: 99%